2022
DOI: 10.3390/agronomy12123074
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Assessment of Sweetpotato Germplasm in China Using InDel Markers

Abstract: Sweetpotato (Ipomoea batatas (L.) Lam.), whose roots are rich in starch, is widely grown around the world and plays a prominent role in ensuring food security. At present, there are no reports on the genetic diversity of sweetpotato germplasm revealed by InDel markers. In this study, we developed a set of 30 InDel markers to evaluate the genetic diversity and relationships of 240 accessions, comprising 77 landraces, 80 introduced accessions, 82 improved varieties released in China, and a diploid wild relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…The clustering results were similar to other economic species such as Lagenaria siceraria [71] and Ipomoea batatas [26,72]. This may be due to H. acerba germplasm's integration with birds, animals, and humans [17,18,72], and, on the other hand, it may be because the H. acerba traits are regulated by internal heritability and the external environment [73]. Therefore, it is necessary to consider not only the geographical source but also the group affiliation when carrying out H. acerba breeding.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The clustering results were similar to other economic species such as Lagenaria siceraria [71] and Ipomoea batatas [26,72]. This may be due to H. acerba germplasm's integration with birds, animals, and humans [17,18,72], and, on the other hand, it may be because the H. acerba traits are regulated by internal heritability and the external environment [73]. Therefore, it is necessary to consider not only the geographical source but also the group affiliation when carrying out H. acerba breeding.…”
Section: Discussionsupporting
confidence: 76%
“…An analysis of the groups showed that 31 H. acerba germplasms did not cluster together according to their geographical distribution. The clustering results were similar to other economic species such as Lagenaria siceraria [71] and Ipomoea batatas [26,72]. This may be due to H. acerba germplasm's integration with birds, animals, and humans [17,18,72], and, on the other hand, it may be because the H. acerba traits are regulated by internal heritability and the external environment [73].…”
Section: Discussionsupporting
confidence: 69%